Sociolegal Analysis of Child Marriage Prevention Policies in Rural Indonesia - Zubaedah Zubaedah (The Indonesian Journal of Sociolegal Development, 2026)
Child marriage continues to pose significant social, legal, and developmental challenges in Indonesia, particularly in rural areas where cultural traditions, economic pressures, and limited educational opportunities influence marriage practices. This study examines the effectiveness of child marriage prevention policies in rural Indonesia through a sociolegal analysis that explores the interaction between legal norms and social realities. Using a qualitative sociolegal methodology, the research analyzes legislative reforms, government programs, and community responses aimed at reducing child marriage prevalence. The findings indicate that legal reforms raising the minimum age of marriage have strengthened the normative framework for child protection. However, implementation challenges persist due to deeply rooted cultural values, religious interpretations, poverty, and limited institutional capacity. The study reveals that legal regulation alone is insufficient to prevent child marriage when social and economic factors continue to encourage early marriage practices. Community engagement, educational initiatives, and economic empowerment programs play a crucial role in supporting policy effectiveness. Furthermore, collaboration among government agencies, religious leaders, educational institutions, and civil society organizations enhances the legitimacy and acceptance of prevention measures. The research argues that sociolegal approaches provide a more comprehensive understanding of child marriage by recognizing the dynamic relationship between law and social behavior. The study concludes that sustainable reductions in child marriage require integrated strategies that combine legal enforcement with social transformation and community-based interventions. These findings contribute to policy discussions concerning child protection, gender equality, and legal development in rural Indonesia.